PENGARUH Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Hasil Belajar Siswa Kelas XI Pada Materi Laju Reaksi - Arafah, Nur; Loka, I Nyoman; Firmansyah, Dodiy (Chemistry Education Practice, 2025)
This research aims to determine the effect of the problem-based learning model on the learning outcomes of reaction rate material in class XI students at SMAN 1 Lingsar. The type of research employed is a quasi-experiment, specifically a non-equivalent control group design. The population in this study consisted of all the students in class XI MIPA at SMAN 1 Lingsar, totaling 143 students divided into 4 classes. The sampling technique used is purposive sampling. The samples in this study were class XI MIPA 2 as the experimental class and XI MIPA 3 as the control class. The experimental class employs a problem-based learning model, while the control class utilizes a conventional learning model. The student learning outcomes were focused on the reaction rate material in the cognitive domain. The data analysis test used in this study is the t-test Gain. The gain in the experimental class (0.47) was greater than the gain in the control class (0.28). The analysis results showed that tcount (3.45) > ttable (2.03) at the 5% significance level, indicating a positive and significant effect of the problem-based learning model on the learning outcomes of reaction rate material for class XI students at SMAN 1 Lingsar.